DEVELOPMENT STRATEGY FOR FISHERY ACTIVITIES IN THE NUSANTARA FISHERY PORT (PPN) PEKALONGAN, CENTRAL JAVA PROVINCE - Hidayat, Syarif; Noviyanti, Rinda; Warlina, Lina (Aurelia Journal, 2023)
The fishing port is a key infrastructure of fisheries management to support the economy of a region and improve the welfare of coastal communities. The fishing port must be able to serve or support the activities of fishing vessels, either landing fish or going to sea with the support of existing facilities. The purpose of this research is to formulate a strategy to increase fishery activity at the Nusantara Fishery Port (PPN) Pekalongan. The data used are primary data and secondary data. Data collection techniques were carried out by observation and interviews, as well as additional data in the form of literature studies. Analysis of the data used is descriptive analysis and SWOT analysis (strengths, weaknesses, opportunities, and threats). The results showed that in formulating a strategy to increase fishery activities in PPN Pekalongan, the identification stage was carried out on internal factors as well as external factors. Based on the SWOT analysis, the data on the internal and external analysis of each factor are summarized as follows: 1. Total Strength Score = 1.871; 2. Total Weakness Score = 0.934; 3. Total Odds Score = 1,546; and 4. Total Threat Score = 1.005. The S-O strategy is implemented by implementing increased publication of potential ports to attract investors in investing in PPN, increasing cooperation between the management and supervisory agencies in the field of supervision of fishery resources and also developing the Pekalongan PPN by building the required fishing port facilities.